BUSINESS OF FISH SEED DISTRIBUTION IN THE SIMPANG TIGA SUB DISTRICT OF PEKANBARU CITY OF RIAU PROVINCE - Yolanda, Halimah Dwi; AN, Darwis; Hamid, Hamdi Hamid3 (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK               This research was conducted in May 2017 which is located in the Simpang Tiga Sub-district Pekanbaru City Riau Province. This study aims to calculate the development of how much investment in fish seed distribution business, to calculate how much revenue and profit distribution of fish seed business and to determine the level of feasibility in the business of fish seed distribution in Marpoyan Damai Bukitraya District Pekanbaru Municipality Riau Province. The method used in this study is the Case Study Method with the number of respondents as many as 4 people.               Fish seed distribution business in the Simpang Tiga Bukitraya Subdistrict Pekanbaru City consists of three types of fish seeds, the type of seed is the fish seed Mas, Nila fish seed and Gurami fish seed, and each year develops, the development can be seen from the total investment issued for distribution fish seeds in the Simpang Tiga District Pekanbaru City Riau Province for Rp. 1.807.145.000, the components that affect the investment is a component of fixed capital and working capital is the manufacture of ponds, water installation, purchase scales, buckets, nets, nets, purchase of chalk, seed purchases, purchase of feed pellets, purchase of additional feed, work. The revenue from fish seed distribution business amounted to Rp.2.209.900.000 every year, while the profit is Rp. 483,755,000 every year, and fish seed distribution business in the Simpang Tiga District Pekanbaru City Riau Province is feasible to be done based on Return Cost Ratio (RCR) value equal to 1.26, Financial Rate of Return (FRR) value 26,76% and  Payback Period of Capital (PPC) 3,73 period, fish seed is distributed to area around Pekanbaru , around Riau, and between provinces namely Riau Islands (Natuna), Jambi, and South Sumatra. Key Word : Business, Distribution, Investment, Fish Seed, Feasible